Case report: Metastatic gastric squamous cell carcinoma with long duration of complete response via three-staged radical concurrent chemoradiotherapy - Rui Zang; Linpeng Zheng; Lijiao Xie; Liangzhi Zhong; Jianguo Sun (Heliyon, 2024)
Introduction: Primary Gastric Squamous Cell Carcinoma (GSCC), especially in late-stage, is a very rare pathological type with poor prognosis. We report a long duration of Complete Response (CR) of GSCC case with multiple metastases by an elaborate three-staged radical Concurrent Chemoradiotherapy (CCRT). Case presentation: A 36-year-old male suffered from weakness and melena, and then was diagnosed as primary GSCC with cT3N3M1, Stage IV. According to the characteristics of multiple lymph nodes metastases at supraclavicular, perigastric and pelvic regions, an individualized therapeutic strategy of three-staged radical CCRT was elaborately designed and cautiously performed even after the accidental massive hemorrhage of the upper digestive tract under the guidance of a multidisciplinary team. A long-term CR was achieved, with Progression Free Survival (PFS) and Overall Survival (OS) of 74 months by the last follow-up. The case with multiple metastases was radically treated as local advanced disease with complete success. Conclusion: Patient with stage IV mGSCC who has achieved CR and unexpected long-term PFS and OS through CCRT due to precise judgement and well-designed individualized therapy. The immunomodulatory effect of radiation therapy on the tumor microenvironment may be a potential mechanism affecting treatment efficacy.